The impact of energy prices on green innovation: Study on behalf of the Swiss Federal Office of Energy SFOE - Marius Ley; Tobias Stucki; Martin Woerter (ETH Zurich, KOF Swiss Economic Institute, 2013)
Based on patent data and industry specific energy prices for 18 OECD countries over 30 years we investigate on an industry level the impact of energy prices on green innovation activities. Our econometric models show that energy prices and green innovation activities are positively related and that energy prices have a significantly positive impact on the ratio of green innovations to non-green innovations. More concretely, our main model shows that a 10% increase of the average energy prices of the previous five years results in a 2.7% and 4.5% increase of the number of green patents and the ratio of green patents to non-green patents, respectively. We also find that the impact of energy prices increases with an increasing lag between energy prices and innovation activities. Robustness tests confirm the main results. – – In der vorliegenden Studie untersuchen wir, gestützt auf Patentdaten und industriespezifischen Energiepreisen für 18 OECD-Länder, den Einfluss von Energiepreisen auf die Innovationstätigkeit in grünen Technologien. Unsere ökonometrischen Schätzungen zeigen eine positive Korrelation zwischen Energiepreisen und grüner Innovationstätigkeit; Energiepreise haben einen signifikant positive Einfluss auf die Quote von grünen im Vergleich zu nicht-grünen Innovationen. So zeigt unser Hauptmodell, dass eine Erhöhung um 10% der durchschnittlichen Energiepreise über fünf Jahre zu einer um 2.7% höheren Anzahl grüner Patente, beziehungsweise einer um 4.5% höheren Quote von grünen Patenten im Vergleich zu anderen Patenten führt. Mit zunehmendem zeitlichen Abstand zwischen Energiepreisen und Innovationstätigkeit lässt sich ein grösserer Effekt der Energiepreise feststellen. Unsere zentralen Resultate werden durch diverse Robustheitstests bestätigt.
Keywords: O30; O34; Q55; 330; innovation; patents; environment; technological change; energy prices; Innovation; Patent; Energiepreis; Technischer Fortschritt; OECD-Staaten